Penanganan Permukiman Kumuh Dengan Pendekatan Kolaboratif Berbasis Collective Action - Muhammad, Ummu Kultsum; Fadila, Rizkiyah Amaliah (Prodi PWK Universitas Tadulako, 2025)
Rapid urban development has led to urbanization, which often triggers the emergence of slums in urban areas. Addressing slum areas requires a comprehensive and collaborative approach, as the challengees lie not only in physical aspects but also in weak institutional roles, government capacity, and community involvement. One approach that can be used is collective action, where the government, private sector, NGOs, and the community form a coalition for a common purpose in addressing slum areas. This study aims to analyze the handling of slum settlements through a collaborative approach based on collective action. The method used is descriptive qualitative with data collection techniques through literature study. The case study of Kampung Pisang in Makassar shows the success of this approach. The Makassar City government, the ministry of public works and housing, and the ministru of social affaris were actively involved, while NGOs and civil society organizations supported the program through advocacy and funding. The success of the program was due to good communication between institutions, which strengthened collective action and formed an effective coalition. Additionally, the local community plays a central role as part of the solution, not merely as recipients of the program. In this study, residents of Kampung Pisang are viewed as part of the urban community with the right to adequate housing and a healthy environment. This research underscores the importance of collaborative governance for the sustainability of slum management.